Microstructural development of hypoeutectic Zn–(10–40)wt%Sn solder alloys and impacts of interphase spacing and macrosegregation pattern on hardness - Santos, Washington L.R.; Brito, Crystopher; Bertelli, Felipe; Spinelli, José E.; Garcia, Amauri (Journal of alloys and compounds, 2015)
The most relevant range of compositions of Zn–Sn high-temperature solder alloys remains between 10 and 40 wt%Sn. Hence, transient directional solidification experiments have been carried out with Zn–10, 20, 30 and 40wt%Sn alloys under a wide range of cooling rates (T˙) with a view to investigating the corresponding microstructural evolution. The microstructure is shown to be formed mainly by an alternation of Zn-rich plate-like cells and a eutectic mixture. Morphological instabilities of the Zn-rich plates are shown to start for the lower content Zn–10 and 20wt%Sn alloys, however a microstructural transition of these plates into cylindrical-type horizontal cells can only be found in the microstructure of the 30 and 40wt%Sn alloys. Experimental growth laws are proposed relating the microstructural spacing (λ) to solidification thermal parameters. Hardness (HV) is shown be affected by both the positive segregation of Sn, the alloy volumetric fraction of Zn and λ. Hall-Petch type equations are proposed relating HV to λ. Schematic representation and corresponding SEM sequential images of morphologies of a hypoeutectic Zn–30wt%Sn alloy considering the growth of the α-Zn phase: (a); (d) plate-like aligned cells; (b); (e) wavy lateral instabilities and (c); (f) formation of a sequence of cylinder-like horizontal bars. [Display omitted] •Plate-like cells become horizontal cylindrical-like cells with increasing Sn content.•For Zn(10; 20%)Sn alloys a –1/4 exponent relates λ to the cooling rate.•For Zn(30; 40%)Sn alloys a –1/2 exponent relates λ to the cooling rate.•Hardness depends on the balance between Sn segregation and λ value for DS Zn–Sn alloys.